Probabilistic assessment of investment options in honey value chains in Lamu county, Kenya - Wafula, Joshua; Karimjee, Yusuf; Tamba, Yvonne; Malava, Geoffrey; Muchiri, Caroline; Koech, Grace; Leeuw, Jan de; Nyongesa, Josephat; Shepherd, Keith D.; Luedeling, Eike (Frontiers Media, 2018)
How to approve and prioritize among projects that aim at biodiversity conservation has been highlighted as one of the most critical decisions that conservation planners face [1]. This is not surprising, because conservation outcomes are often achieved through complex mechanisms, and the success of conservation actions is rarely guaranteed, with many uncertainties preventing precise impact prediction. Success is even harder to predict, when conservation agencies aim to strengthen biodiversity indirectly, e.g., by supporting livelihoods and economies of local people as an incentive for them to conserve biodiversity outcomes [2]. Investing in biodiversity based value chains does not necessarily result in positive biodiversity outcomes. Negative impacts can arise, when value chain development results in depletion of the biodiversity that forms the resource base, on which the value chain depends (e.g. fisheries or non-timber forest products).